The use of rhBMP in spine surgery: is there a cancer risk? - DeVine, John G.; Dettori, Joseph R.; France, John C.; Brodt, Erika; McGuire, Robert A. (Evidence-Based Spine-Care Journal, 2012)
Study design: Systematic review.Study rationale: Some have noted several safety issues associated with the use of bone morphogenetic proteins (BMPs), including cancer risk, stating both BMP and their receptors had been isolated from human tumors. In addition, data presented to the US Food and Drug Administration (FDA) on the product AMPLIFY™ (rhBMP-2, 40 mg) revealed a higher number of cancers in the investigational group compared with the control.Objective: To independently review the cancer risk of rhBMP-2 use in spine fusion as published in the peer-reviewed literature and in the publicly available FDA data summaries.Methods: A systematic review of the literature was undertaken for articles published through January 2012. Pubmed, Cochrane, National Guideline Clearinghouse Databases as well as bibliographies of key articles were searched. Two independent reviewers revised articles. Inclusion and exclusion criteria were set and each article was subjected to a predefined quality-rating scheme.Results: Five published peer-reviewed studies and two FDA safety summaries reported the occurrence of cancer in patients treated with spinal fusion using rhBMP-2 or rhBMP-7. Cancer data for on-label use of rhBMP-2 (InFUSE™) were reported in the FDA data summary but not in one published pivotal study. The risk of cancer was same in both the rhBMP-2 and control groups, 0.7% after 24 months. Off-label use of rhBMP for posterolateral fusion (PLF) was associated with a slightly higher risk of cancer compared with controls in three randomized controlled trials and one poorly conducted retrospective cohort study at various follow-ups. In PLF the risk of cancer was 3.8% using 40 mg of BMP-2 compared with 0.9% in the control group. Two RCTs evaluating rhBMP-7 reported a cancer risk of 12.5% and 5.6% in the rhBMP-7 group compared with 8.3% and 0% in the control groups, respectively. The differences in these studies were not statistically significant; however, the sample sizes for these studies were small.Conclusions: Cancer risk with BMP-2 may be dose dependent, illustrating the need to continue to study this technology and obtain longer follow-up on patients currently enrolled in the FDA trials. Additionally, refined guidelines regarding the routine use of BMPs should be developed, taking into account the FDA summary data that is not routinely scrutinized by the practicing surgeon.